MEMAHAMI â€œBETAWIâ€ DALAM KONTEKS CAGAR BUDAYA CONDET DAN SETU BABAKAN - Ana Windarsih (LIPI Press, 2013)
To know â€œBetawiâ€ is interesting, but complex, as researchers and observers view â€œBetawiâ€ according to their scientific background. The question about â€œBetawiâ€, who they are and how is the condition of â€œBetawiâ€ lead to Jakartaâ€™s government policies for cultural conservation for securing â€œBetawiâ€. Theâ€œCagar Budaya Condetâ€ and â€œSetu Babakanâ€ is case study using in depth interview and observation for explaining and understanding the identity questions. The finding is the â€œBetawiâ€ still exist and secured at Setu Babakan as â€œCagar Budaya Condetâ€ which were previously being estimated would be unsuccessful effort. Keywords: betawi, Condet cultural conservation and Setu Babakan